Pemanfaatan Legenda Singocandi Sebagai Penanaman Nilai Budaya untuk Siswa Sekolah Dasar Media Komik Digital - Aulia Sava Kamila; Irawan Setyo; Fearla Ranta Ranmayli; Luthfa Nugrahani (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
Instilling cultural values in elementary school students is one of the important strategies in character education based on local wisdom. Local legends, such as the singocandi legend, can be integrated into learning through interesting media, one of which is digital comics. This study aims to systematically examine how local legends are used in digital comic media to instill cultural values in elementary school students. The method used is the Systematic Literature Review (SLR) by following the stages of identification, screening, eligibility, and synthesis of data from relevant articles. The results of the study indicate that folklore in digital media can instill cultural values such as courage, honesty, and responsibility. In addition, the study shows that digital comics have the ability to increase student engagement and understanding of local cultural content. So, digital comics based on local legends are a good learning strategy for the younger generation.